Influence of social phenomena on the increase in port- necrotic cirrhosis in Lima. Caused by viral hepatitis - Vega Rizo Patrón, Leoncio (1967)
A comparative statistical study of the incidence of fatal hepatitis ( massive hepatic necrosis ) , liver cirrhosis and primary liver cancer , has been done in the autopsies on the " Archbishop Loayza" Hospital, for the period November 1961 to August 1966. The incidence of these diseases in this hospital during the indicated period compared with that found in the same hospital in previous autopsy series . We have found that in the last 20 years there was a progressive increase in the incidence of fatal viral hepatitis deaths ( massive hepatic necrosis) of 0.06 % to 2.4 %. We believe that this increase could be related to the development , in the same period of unhealthy marginal areas of the city. We also found that the predominant type of cirrhosis among us is the post- necrotic (52.8 %) , which possibly is related to the high incidence of hepatitis. Finally we find that the proportional frequency of primary liver cancer among us is high.